Educação profissional em saúde : as percepções dos agentes comunitários de saúde no município de Itabaiana-SE - Tenório, Flávia Priscila Souza (2011)
This study aims to analyze the contributions of Community Healthcare Agent Training Course s Stage I, through the perception of these students /workers included in the referred training in the city of Itabaiana, state of Sergipe in 2010. By understanding that the demand for this training is related to political, ideological and social choices inserted in a particular context, we sought to conduct a historical review of the Health Professional Education articulated with the policies and laws of the Ministry of Education. To carry out the research, we had chosen quantitative and qualitative study by using focus groups, in addition to document analysis, in order to understand which contribution the Training Community Healthcare Agent (CHA) brings to the daily work of professionals within the National Health System, from the perspective of these subjects. The analysis of the focus groups was framed along the following lines: the work of the Community Healthcare Agent, the participation of CHAs in Stage I of the training course and the perception of CHAs over the training course for the work process of these professionals. Finally, we present the links between the reading of documents seized in the analysis and the discourse of CHAs on the Training they were offered, focusing on the development achieved (or not) through this training experience for both CHAs, living and working in urban areas and those in the rural town of the city of Itabaiana-SE.